Influence of Long Term Oral Anticoagulants upon Prothrombin Fragment 1 + 2, Thrombin-Antithrombin III Complex and D-Dimer Levels in Patients Affected by Proximal Deep Vein Thrombosis - Elias, A; Bonfils, S; Daoud-Elias, M; Gauthier, B; Sié, P; Boccalon, H; Boneu, B (Thrombosis and Haemostasis, 1993)
We have investigated the influence of long term oral anticoagulants (OAC) upon the plasma levels of prothrombin fragment 1 + 2 (F1 + 2), of thrombin-antithrombin III complexes (TAT) and of D-Dimer in 20 patients affected by a proximal deep vein thrombosis (DVT) diagnosed by ultrasonic duplex scanning. Patients (63 ± 17 years, mean ± SD) were sampled at the beginning of the OAC treatment (day 1), which was started 1 to 6 days after diagnosis confirmation and full heparinization, and then 8, 35 and 92 days after. The results were compared to those obtained in a blood donor population (39 ± 10 years) and to an age-matched healthy population (63 ± 19 years). The mean INR determined on days 8, 35 and 92 were almost identical (2.8 ± 0.7, 2.9 ± 0.9 and 2.8 ± 0.6 respectively). In contrast, highly significant variations of the three markers were recorded during the observation period. Eight days after the beginning of OAC, increased levels of TAT complexes were associated with subnormal levels of F1 + 2 suggesting persistence of a hypercoagulable state. On the further sampling times, TAT complexes were in the normal range while F1 + 2 were far below the normal range. Between day 1 and day 92, the levels of D-Dimer continuously decreased reflecting a long-term fibrinolytic process.This study clearly indicates that high INR are not systematically associated with very low F1 + 2 levels, particularly in the acute phase of thrombosis. Whether or not it is possible to reduce the intensity of the anticoagulant treatment 1 month after its initiation on the basis of very low levels of F1 + 2 can only be determined by prospective clinical trials.